Serum Homocysteine Level Predictive Capability for Severity of Restenosis Post Percutaneous Coronary Intervention - Guo, Jiqiang; Gao, Ying; Ahmed, Mohammad; Dong, Pengfei; Gao, Yuping; Gong, Zhihua; Liu, Jinwen; Mao, Yajie; Yue, Zhijie; Zheng, Qingli; Li, Jiansheng; Rong, Jianrong; et al. (Frontiers in Pharmacology, 2022)
Background: In stent restenosis (ISR) is one of major complications following stent implantation. There is growing interests to identify a biomarker of the ISR. High levels of serum homocysteine (Hcy) have been associated with cardiovascular disease. The purpose of this study was to quantify the correlation between serum Hcy and the severity of ISR. When compared with coronary angiography (CAG), Hcy levels provided a significantly better clinical detection of ISR severity after PCI. Methods: 155 patients ranging from 6 months to two years following PCI were sampled from Shanxi Bethune hospital. Serum Hcy levels and postoperative angiography results were used to differentiate the patients into two groups: ISR and non-ISR. The non-ISR include two subgroups: intimal hyperplasia (10-50% diametrical stenosis), and recovery (<10% diametrical stenosis). Results: The level of serum Hcy in the experimental group was higher than that of the control group. The serum Hcy level in the restenosis group was higher than the intimal hyperplasia group. The no plaque group portrayed a slightly higher serum Hcy level than the control group. The incidence of ISR was 5%, 6.25%, 7.5% and 15%, in the quartiles respectively. The correlation between serum Hcy level and the severity of ISR in the experimental group was analyzed by the Pearson correlation test. The serum Hcy level in the experimental group was (20.21±11.42) μmol/L, the severity of in stent restenosis was (0.25±0.31), R value was 0.234 and p value was 0.037. Taking coronary angiography as the gold standard, an ROC curve analysis was performed on the serum Hcy levels in the experimental group. The area under the curve (AUC) was 0.718 (95% CI 0.585-0.854, p<0.001), indicating that the serum Hcy concentration could predict ISR. On the ROC curve, the best critical value of serum Hcy concentration for predicting ISR was 20.05 μmol/L, with a sensitivity of 45% and specificity of 88.1%. Conclusion: There is a positive correlation between homocysteine and the severity of restenosis after PCI, and the level of Hcy could serve as a predictive biomarker for the severity of ISR.